TOTAL QUALITY MANAGEMENT(TQM) DALAM KONTEKS PENDIDIKAN - Huri, Daman (AS-SALAM, 2012)
Total quality managent is a proces of continuously improvement done by a school in getting shool quality. Manager has important role in cloing, implementry TMQ in the school. The head master need to understand TMQ as a philosophy, method, techniqve and strategy of managent to improve school quality because the way of school organization work is always assessed by communites howdays TMQ in education aspect plees the students as cliens so that students idea must be included in every strategy dieision making school organization. Besides,the head master is not the main mass in improving the quality, but every one given responsibility is a manager and having a right to take a decision in every their responsibilityÂ Key word : Total Quality Managenent, Pendidikan,Manajer.